(untitled) (Open Herald: Periodical of Methodical Research, 2024)
Modern linguistics, which is fundamental to learning the Arabic language, is a crucial part of the process. This project will seek to understand how the teaching of the Arabic language through modern linguistic technologies has affected the learning of the language through contemporary means. This study applies descriptive and qualitative methods, resulting in a qualitative approach based on descriptive methods applied after descriptive methods, and on the application of descriptive methods. Modern linguistics is a means of acquiring skills like phonological analysis, comprehension, applying, and analyzing principles of phonological in studying systems sound in Arabic. The. Specifically, to understand structures morphological, eye meanings, word formation rules, morphological patterns and morphological variations, in Arabic; to analyze sentence and syntax structure in greater detail; to analyze semantics and word meanings in language; to analyze semantics and semantic patterns in language; and to analyze semantics and word meanings in language; and preferably, to include semantics and word meanings in language; to incorporate semantics and word meanings in language; and preferably, to analyze semantics and word meanings in language, Through logical analysis and semantics, morphological and morphologically related semantics, morphological and morphological patterns, morphological analysis and morphological analysis, morphological analysis and morphological analysis, and morphologically related situations in general, morphological events, morphological variations, morphological variations, and so on, it is possible to gain a comprehensive comprehension of language and its role in communicative and social interactions through pragmatic scrutiny and analysis of language. Modern linguistics emphasizes morphological analysis phonological analysis, and word formation, analysis of sentence and syntax structure, analysis of word and semantics meanings, and use of language and pragmatic analysis, rather than relying solely on linguistics